2009
DOI: 10.1186/1471-230x-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin and CRP levels in non-alcoholic fatty liver disease: a case control study

Abstract: BackgroundBoth C reactive protein (CRP) and procalcitonin (PCT) are well known acute phase reactant proteins. CRP was reported to increase in metabolic syndrome and type-2 diabetes. Similarly altered level of serum PCT was found in chronic liver diseases and cirrhosis. The liver is considered the main source of CRP and a source of PCT, however, the serum PCT and CRP levels in non-alcoholic fatty liver disease (NAFLD) were not compared previously. Therefore we aimed to study the diagnostic and discriminative ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
5
43
1
Order By: Relevance
“…In addition, high level of CRP was also used for the prediction of metabolic syndrome, T2DM, and coronary heart disease [46,47]. Despite the controversial opinions, there are still several studies identified the association between high levels of CRP and NAFLD [48][49][50]. In this study, liraglutide was more effective than metformin at decreasing the levels of CRP.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, high level of CRP was also used for the prediction of metabolic syndrome, T2DM, and coronary heart disease [46,47]. Despite the controversial opinions, there are still several studies identified the association between high levels of CRP and NAFLD [48][49][50]. In this study, liraglutide was more effective than metformin at decreasing the levels of CRP.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, dogs with congenital portosystemic shunts (CPSS) that have hepatic encephalopathy were shown to have higher serum CRP concentrations than those without hepatic encephalopathy (Gow et al ). Increased serum CRP concentrations have also been reported in human patients with hepatic neoplasia (Zheng et al ) and non‐alcoholic steatohepatitis (Oruc et al ). To the authors’ knowledge, serum CRP concentrations have not been evaluated and reported in dogs with hepatic diseases other than CPSS.…”
Section: Introductionmentioning
confidence: 81%
“…The Oruc N et. Al 20 group study showed increase in mean serum CRP level was increased in NAFLD compared to controls. CRP can be used as an additional marker for diagnosis of NAFLD group.…”
Section: Discussionmentioning
confidence: 88%